Android Based Learning Media Busuu for German Self-Learning - Avrisa Ramadhania Moh. Yamin (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
This research aimed to describe the use of Busuu android-based media for self-learning for X Language Class SMA Laboratorium UM students and to know the students responses to the use of this media. This research used descriptive qualitative method. The data sources of this research were the activities of 20 students from X Language Class and the students self. The data collection was obtained using observation and questionnaire sheets. The results of this research indicate that use of Busuu android-based media run well. Students can more understand easily of German language material and class conditions are also controlled during learning process. Based on this description, Busuu can be used as an alternative learning media for German Language self-learning.